The non-identity problem and the ethics of future people - Boonin, David (Oxford University Press, 2014)
David Boonin presents a new account of the non-identity problem: a puzzle about our obligations to people who do not yet exist. Our actions sometimes have an effect not only on the quality of life that people will enjoy in the future, but on which particular people will exist in the future to enjoy it. In cases where this is so, the combination of certain assumptions that most people seem to accept can yield conclusions that most people seem to reject. Thenon-identity problem has important implications both for ethical theory and for a number of topics in applied ethics, including controversia.